Pearls to Address Challenges in Initial Casting Treatment for Idiopathic Clubfoot - Christopher Williams, BS; Patrick Nian, BA; Ruth H. Jones, BS; Amith Umesh, BA; David M. Scher, MD; Shevaun M. Doyle, MD (Journal of the Pediatric Orthopaedic Society of North America)
ABSTRACT: Ponseti casting has established itself as the gold standard for the treatment of clubfoot over the past 30 years due to its outstanding short- and long-term outcomes. This method requires a nuanced technique throughout each phase of correction, involving gentle manipulation of the appropriate anatomic regions of the foot. Certain “pearls” should be considered to optimize this process, including minimizing infantile distress, deliberately choosing casting and padding material, and planning the casting timeline. Clubfoot providers should be aware of the “pitfalls” associated with inadequate execution of casting, including cast slippage, overcorrection, skin manifestations, and residual deformity. Key Concepts: (1) Ponseti casting addresses all elements of clubfoot (midfoot cavus, forefoot and midfoot adduction, hindfoot varus, and equinus) in a systematic way that respects the natural kinematics of the foot. (2) Ponseti casting requires the use of gentle manipulation through the appropriate anatomical regions of the foot to ensure adequate correction, minimize residual deformity, and avoid iatrogenic deformity. (3) Efforts to minimize infantile distress will maximize the success of the Ponseti method. These include choosing appropriate cast and padding materials, providing a succinct casting plan, and optimizing brace tolerance. (4) Common undesirable consequences of casting include cast slippage, skin maceration, and iatrogenic deformities, such as tarsometatarsal abduction, hindfoot valgus, rocker bottom foot, and flat-top talus.